IMPLEMENTASI PROGRAM KARTU PRAKERJA DI KECAMATAN PARIGI KABUPATEN GOWA - Bakhtiar Bakhtiar; Mustari Mustari; Eka Pratiwi Syam (Jurnal Tomalebbi, 2023)
Abstrak : This study aims to: (1) Determine the requirements and procedures for registration of the pre-employment card program in Parigi sub-district, Gowa district. (2) Knowing the supporting and inhibiting factors of the community to participate in the pre-employment card program in Parigi sub-district, Gowa district.(3) Knowing the government's efforts in helping the community to participate in the pre-employment card program.the following results: (1). In general, the requirements and procedures for registering the pre-employment card program in the Parigi sub-district, Gowa district, have been fulfilled by almost all registrants. (2). The factors that influence the community in participating in the pre-employment card program are generally divided into 2, namely supporting factors and inhibiting factors. The supporting factors themselves consist of daily needs, high incentives, and support from the government. Meanwhile, the inhibiting factor itself consists of low expertise in using devices or technology, and the poor system of the pre-employment card itself which sometimes makes it difficult for registrants to register. (3). There are several efforts made by the government in the Parigi sub-district, Gowa Regency in supporting the community to participate in programs held by the government such as the pre- employment card program, including by conducting socialization, and providing good services to people who need complete registration files.Keywords: Implementation, Program, and Pre-Employment CardAbstrak : Penelitian ini bertujuan untuk: (1) Mengetahui syarat dan prosedur pendaftaran program kartu prakerja di kecamatan parigi kanupaten gowa. (2) Mengetahui faktor pendukung dan penghambat masyarakat untuk ikut program kartu prakerja di kecamatan parigi kabupaten gowa. (3) Mengetahui upaya pemerintah dalam membantu masyarakat untuk ikut program kartu prakerja. hasil sebagai berikut: (1). Secara umum persyaratan dan prosedur dalam pendaftaran program kartu prakerja di kecamatan parigi kabupaten gowa sudah dipernuhi oleh hampir semua pendaftar, saat melakukan pendaftaran juga mereka sudah melakukannya sesuai dengan prosedur yang telah ditentukan. (2). Adapun faktor yang mempengaruhi masyarakat dalam mengikuti program kartu prakerja secara umum dibagi menjadi 2 yaitu faktor pendukung dan faktor penghambat faktor pendukung itu sendiri terdiri dari adanya kebutuhan sehari-hari, adanya insentif yang tinggi, serta adanya dukungan dari pemerintah. Sementara untuk faktor penghambat itu sendiri terdiri atas rendahnya keahlian dalam menggunakan perangkat atau tekhnologi, serta kurang baiknya sistem dari kartu prakerja itu sendiri yang terkadang membuat para pendaftar kesulitan dalam mendaftar. (3). Terdapat beberapa upaya yang dilakukan oleh pemerintah di kecamatan parigi kabupaten gowa dalam mendukung masyarakatnya untuk mengikuti program yang diadakan oleh pemerintah seperti halnya program kartu prakerja ini diantaranya adalah dengan mengadakan sosialisasi, dan memberikan layanan yang baik kepada masyarakat yang membutuhkan kelengkapan berkas pendaftaran.Kata Kunci: Implementasi, Program dan Kartu Prakerja